EVALUATION OF INTEGRATED COUNSELING POST SERVICES FOR NON-COMMUNICABLE DISEASES AT SINGGANI COMMUNITY HEALTH CENTER - Hinelo, Evi; Irfan Mufti, Mohammad; Asrifai, Asrifai (Penerbit Lafadz Jaya, 2024)
Non-communicable diseases (NCDs) remain a significant health issue that requires proper management. Data from the Central Sulawesi Provincial Health Office indicates a continued rise in NCD cases, with 39,961 cases reported in 2021, increasing to 51,805 in 2022. This study aimed to evaluate the integrated NCD development post services at the Singgani Health Center in Palu City. Using a qualitative research method and a descriptive analytical approach, three informants were interviewed: a program holder, a cadre of the Integrated Service Post (Posbindu), and a participant. Data were collected through in-depth interviews, observations, and document reviews. The findings revealed that the implementation of human resources, facilities, recording, and reporting is still suboptimal. Cadres’ skills are not yet fully developed, and there are gaps in essential facilities, such as missing height measuring instruments and waist circumference tools. The Integrated Service Post has also not adopted the 5-table system as per standard procedures. However, budget allocation and planning have been satisfactory, including transportation arrangements for cadres and staff. The study concludes that the lack of adequate training for cadres and insufficient facilities are disrupting the effectiveness of the service process. To improve, it is suggested that certified training be provided, technical guidelines for the Integrated Service Post be clearly communicated to all cadres, and the 5-table service system be fully implemented to optimize the service process.